EvidenceBased Medicine Presentation Skills and the Quality of Morning Report in Medical Students: An Operations Research - Ehsan Nezakati; Mohammad Bagher Sohrabi; Robabeh Zaroug-Hosseini; Pouneh Zolfaghari; Elaheh Yahyaei (Kerman University of Medical Sciences, 2016)
Background & Objective: The morning report is a common useful and valuable clinical ‎training method in the world This method when applied on the basis ‎of evidencebased medicine (EBM) plays a more effective role in learning among medical ‎students This study aimed to determine the impact of EBM on medical students skill in ‎presentation of morning report and its quality‎ Methods: This study was operations research and 80 students were selected through simple random sampling ‎from among all medical practitioners of Shahroud University of Medical ‎Sciences (Iran) The selected participants took part in the 3day workshop of introduction to ‎EBM with emphasis on morning report presentation Data were gathered using a researcher‎made questionnaire which was validated by experts and its reliability was approved using ‎Cronbachs alpha coefficient Questionnaires were distributed among the students before and after ‎the study and the results were compared Data were analyzed using chisquared test and ttest in ‎SPSS software‎ Results: Of the 80 interns participating in the study 22 individuals (275%) were men and the rest were female Average ‎time of internship training for the interns was 105 ± 65 months (range: 316 months) The mean quality ‎score of morning increased significantly from 903 ± 256 at baseline to 1328 ± 303 (P ‎‎= 0001) Significant changes were observed in broadband facilities computer ‎facilities and the emergence of new and accessible scientific resources the ‎average number of interns participating in the meeting average attendance of those on ‎duty the night before regular attendance of teachers regular participation ‎of interns the regular and timely attendance of those managing the discussion active participation of interns in discussions role of teachers in the meeting the selection of patients the method of discussion about different parts of the ‎patient followup of previously introduced patients and the positive role ‎of group administrators before and after EBM training‎ Conclusion: Morning reports presentation based on EBM during internship at this ‎University was desirable which can effectively result in the ‎improvement of the quality of education regular and more beneficial attendance of teachers ‎especially onduty specialists and more active participation of students and thus improve care ‎training and update clinical teachers information However due to students and professors lack ‎of knowledge regarding EBM holding training courses on ‎this topic seems necessary‎